Analysis of the Properties and Application Status of Novel Impression Materials in Digital Dental Practice - Meng, Fei; Chen, Yang (International Journal of Materials Science and Technology Studies, 2025)
The advent of digital dentistry has revolutionized traditional workflows, with intraoral scanning (IOS) emerging as a cornerstone for direct digital impression acquisition. However, conventional impression materials remain indispensable, particularly for specific clinical scenarios. This review analyzes the properties and application status of novel impression materials developed for and alongside digital technologies. It focuses on the evolution of polyvinyl siloxane (PVS) and polyether (PE) materials, the emergence of hybrid and modified materials, and the growing role of scannable silicones and 3D printing resins. The article evaluates their key performance characteristics—such as dimensional accuracy, stability, hydrophilicity, and compatibility with digital workflows—and discusses their clinical applications in fixed prosthodontics, removable prosthodontics, and implant dentistry. Finally, the challenges and future trends, including the integration of bi-functional materials and additive manufacturing, are explored.